Evolving Purchasing and Supply Organizations: A contingency model for structural alternatives. Issue 1 (January 2018) - Bals, Lydia; Laine, Jari; Mugurusi, Godfrey
Abstract: Purchasing and Supply Management (PSM) is under significant pressure to find levers to further increase its contribution to corporate goals. In order to improve performance in line with expectations, Purchasing and Supply Organizations (PSOs) have to evolve continuously. To help address this challenge, a comprehensive contingency framework of PSO structures is presented. The framework is based on existing literature on PSO contingency factors as well as analysis of two case companies. The findings highlight the importance of taking a contingency perspective for understanding the PSO and combining a detailed view of macro-level structural dimensions with micro-level characteristics. These macro-level dimensions comprise category, business unit, geography and activity. The micro-level characteristics comprise centralization, formalization, specialization, participation and standardization. From a theoretical perspective, the contingency framework opens up insights that can be leveraged in future studies in the fields of hybrid PSOs, global sourcing organizations, and International Purchasing Offices (IPOs). From a practical standpoint, an assessment of external and internal contingencies and their relation to specific structural dimensions and characteristics provides the opportunity for more consciously evolving the PSO to continue to improve PSM's contribution. Highlights: Purchasing and Supply Organizations (PSOs) have to match external and internal demands A comprehensive contingency framework is derived from literature and two case companies. It features a combined view of the macro-level and the micro-level. Activity is added as a new macro-level dimension from the cases.